Why and How Non-English Department Students Learn Vocabulary in Using Realia - Usman Dilo, Asna (Language Development Center, 2022)
Background: The primary language aspect is vocabulary. It must be mastered before mastering English skills. Vocabulary is the basement component of language proficiency and provides much of the basis for how well learners speak, listen, read, and write. Purpose: This study reported comprehensive findings and interpretations that will provide a deep understanding of why non-English department students learn vocabulary using realia and why they learn the way they do. Method: This research is classroom action research that generally aims to improve students' communicative competence in English Results and Discussion: The results showed that by using realia teaching materials, lecturers could motivate students in communicative competence, and it can be seen in the results of research that have increased significantly. This can be proven by the increasing ability of students to describe things and communicate well and smoothly during the teaching and learning process. Students quickly draw what is happening around them because they are obtained or events that occur in their area. Conclusions and Implications: By using realia teaching materials, lecturers can motivate students in communicative competence, which can be seen from the research results that have experienced a significant increase. This can be evidenced by the increasing ability of students to describe things and communicate well and smoothly during the teaching and learning process. The implication of this research is to motivate students to communicate, and it must start with what exists and happens in the environment where they live so that they can easily find difficult words. The implication of this research is that in motivating students in communicating, it should start from what exists and happens in the environment where they live so that they can easily find difficult words.